Aloe vera extract mediated hydrothermal synthesis of rose-like copper iron sulfide for efficient oxygen evolution reaction - Selvanathan V.; Sarkar D.K.; Mottakin M.; Islam M.A.; Almohamadi H.; Alharthi N.H.; Kiong T.S.; Aktharuzzaman M. (Taiwan Institute of Chemical Engineers, 2024)
Background: Fabricating electrocatalysts with high surface area is salient to attain water splitting reaction with high efficiency. Conventionally, complexing agent assisted hydrothermal synthesis is often used to synthesize electrocatalyst with unique morphologies that could improve the electrocatalytic surface area. Method: In this work, a novel approach of adopting aloe vera extract as green complexing agent was used to fabricate copper iron sulfide (CuFeSx)-based nanostructure on nickel foam. Different ratios of aloe vera extract and water were used to identify the effect of complexing agent on morphology of the material. Significant: findings FESEM micrographs verified the role of aloe vera extract as green complexing agent that formed nanorose-like morphology when 75% aloe vera was used. The optimized composition showed that only 234 mV overpotential was required upon iR-compensation to attain 100 mA cm?2 with a corresponding Tafel slope of 81 mV dec?1. Electrochemical surface area analysis (ECSA) revealed that high surface area exposure aided in lowering the overpotential to achieve high current density. The electrocatalyst exhibited good stability upon sustained exposure to alkaline medium for 48 h, retaining up to 84% of its initial current density. This study highlights the potential of using phytochemical-mediated synthesis to fabricate electrocatalysts for generation of sustainable hydrogen fuel via water splitting. 2023